Desenvolvimento local sustentável : caracterização do APL de artesanato de linha do município de Tobias Barreto SE - Santos, Renata Lima (2007)
The crisis observed in the capitalist model of accumulation over the last 70 years has redefined the importance of flexible production and local competitive advantages. In the 1990s, productive agglomerations gained prominence in the economic literature as an important strategy for economic development, distinguished by the territorial proximity of economic, social, and political agents. From this prerogative, the present work focuses on Local Productive Arrangements. From this context the thesis characterizes the recent evolution of the Local Crafts Productive Arrangement in the city of Tobias Barreto - Sergipe, using data gathered by field research carried out in 2004, 2005 and 2006. To accomplish field research, personal interviews were conducted with structured questionnaires to leaders, presidents and craftsmen from five associations, in order to gather data with reference to the socioeconomic profile of the craftsmen, their life trajectory, the strengthening of the dynamic, the organization of production, and market access, in addition to environmental and cultural aspects. Indicators related to the strengthening of the dynamic have the objective of evaluating the level of cooperation between the associations. In terms of the structure of labor, theories of local sustainable development are presented along with historical transformations that led to the emergence of local development theory. It is stressed the importance of these theories of the contemporary economic structure for the formularization of politics, mainly as relates to the generation of jobs and income in less favored regions, as is the case of the city of Tobias Barreto. The importance of the craft s sector of sustainable as a sustainable alternative for the socioeconomic development is illustrated, highlighting its income-generating capability. Brazil today possesses about 8,5 million craftsmen, who generate more than R$ 54 billion annually, representing an average income of about $6,350 dollars. In the Northeast approximately 2.5 million people are involved with craft s activities. The typology lace and embroidering is most frequent in the Northeast, indicated as a craft s activity in 270 cities, representing 23% of the production of the region. Sergipe is one of the states with a larger prominence in the lace and embroidering categories, and the city of Tobias Barreto gains prominence. The city possesses a tradition in the production and commerce of confections and crafts, especially in embroidering (richeliê), with some establishments starting up in the 1940s. With an agricultural sector subject to an intemperate climate, the economic dynamic of the city is associated with craft s activity, facilitated mainly by the existing labor and the presence of six associative organizations, which help in the organization and cooperation of the local production. As such, the principal conclusive results characterize the local productive arrangement with a good degree of cooperation, and a trend of increasing of income levels, although still significantly below national levels. However, the increased yields of the associations have still not contributed significantly to improve the level of the quality of life. The craft s sector of Tobias Barreto points to a new degree of production and productivity, aiming to increase the productivity of its finishing technique, thus becoming a more competitive and better accepted product in other regions of the country, such as the Southeast. This performance clearly reflects the importance of the introduction of innovations observed in the city. The local productive arrangement constitutes an alternative for the problem of unemployment, characterizing itself by revitalizing traditional economic activities, constituting a strategy for employment generation, strengthening markets, preserving cultural values and amplifying the knowledge of local characteristics and values.